A case of persistent left superior vena cava: an anatomical rarity with clinical implications - Saraswat, Pawan; Prasad, Rajniti; Singh, Ankur; Baranwal, Sandeep Kumar; Kumar, Nitish; Abhinay, Abhishek (International Journal of Contemporary Pediatrics, 2023)
Persistent left superior vena cava (PLSVC) is a rare congenital anomaly characterised by the presence of a persistent left-sided SVC in addition to the normal right-sided SVC. This case report presents a unique instance of PLSVC in a 13-year-old male patient who was incidentally diagnosed during routine cardiac imaging for an unrelated condition. The diagnostic journey, including imaging modalities such as echocardiography and computed tomography, revealed the presence of this anatomical variation. Despite being asymptomatic, the case highlights the importance of recognising PLSVC, as it can have clinical implications in various medical and surgical scenarios, particularly in cardiac catheterization, pacemaker implantation, and central venous access procedures. This report discusses the clinical significance, diagnostic challenges, and management considerations associated with PLSVC, emphasising the need for increased awareness among healthcare professionals to ensure safe and effective patient care.